Nurses' knowledge, attitudes and practices related to physical restraint: a cross‐sectional study. (24th July 2018) - Wang, L.; Zhu, X.‐P.; Zeng, X.‐T.; Xiong, P.
Abstract : Aim: To investigate nurses' knowledge, attitudes and practices related to physical restraint in tertiary hospitals and identify the factors that influence physical restraint use. Background: Physical restraint is used to maintain patient safety. Nurses play an important role in the restraint process. It is important to identify their understanding, feelings and approach regarding the use of physical restraint. Introduction: Physical restraint is widely practiced in hospitals in China. However, it results in a range of serious negative consequences. This article provides a clear description of nurses' knowledge, attitudes and practices related to physical restraint. Methods: A cross‐sectional survey was conducted. The participants were asked to complete a questionnaire examining their knowledge, attitudes and practices related to physical restraint use. A total of 200 questionnaires were distributed in four tertiary hospitals in Hubei Province, China between August and October 2014. Results: The nurses' responses indicated a good level of knowledge regarding physical restraint use. However, they held some misconceptions. The nurses' attitudes towards physical restraint tended to be neutral. The nurses were well experienced in the use of physical restraint. Nurses who had received on‐the‐job training performed better than those who had received no training related to knowledge and practices regarding physical restraint use. Conclusions and implication for nursing/health policy: In‐service training is highly recommended for nursing managers to improve nurses' physical restraint related knowledge and practices. Regulations regarding the use of restraints should be established as soon as possible by healthcare administration system. Implications for nursing: Nurses should be open to evaluate and improve their views and attitudes regarding effective physical restraint use via multidimensional interventions.